Factors affecting plagiarism among students at Jazan University - Elshafei, Hanaa A. (2021)
Examination of the responses of the students to various plagiarism situations showed misunderstandings and misconceptions about many forms of plagiarism. Our study emphasizes that the problem in our society is that students or budding innovators are being pressured to get involved in academic dishonesty in order to perform better. To have a safe environment, the amount of academic misconduct, theft, and plagiarism must definitely be reduced to a minimum.